2019
DOI: 10.3122/jabfm.2019.01.180138
|View full text |Cite
|
Sign up to set email alerts
|

The American Board of Family Medicine's Data Collection Method for Tracking Their Specialty

Abstract: Background: Medical certifying boards' core mission is assuring the public that Diplomates have the requisite knowledge, skills, and professional character to provide high-quality medical care. By understanding their Diplomates' workforce and practice environments, Boards ensure that certification is relevant to the profession and accountable to the public. Current and reliable data are key to meeting this function. The objective of this article was to describe American Board of Family Medicine (ABFM) data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…We used data from the 2017 American Board of Family Medicine (ABFM) Family Medicine Certification Examination registration questionnaire of practicing physicians seeking to continue board certification. 17 The questionnaire is a mandatory component of examination registration and is completed 3 to 4 months prior to the examination date. The questionnaire asks about practice type and ownership, scope of practice, and practice features.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used data from the 2017 American Board of Family Medicine (ABFM) Family Medicine Certification Examination registration questionnaire of practicing physicians seeking to continue board certification. 17 The questionnaire is a mandatory component of examination registration and is completed 3 to 4 months prior to the examination date. The questionnaire asks about practice type and ownership, scope of practice, and practice features.…”
Section: Methodsmentioning
confidence: 99%
“…18 Prior work has shown that respondents to each module have characteristics similar to all examinees. 17 The certification examination is administered twice per year and if registered twice, the most recent responses were analyzed. Physician demographics (age, sex, and degree type) were obtained from ABFM administrative databases.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed data from the 2017 American Board of Family Medicine (ABFM) Family Medicine Certification Examination practice demographic registration questionnaire for those seeking to continue their certification. 29 The questionnaire is a mandatory component of examination registration and is completed 3 to 4 months before examination day. The questionnaire asks about scope of practice, practice organization, practice location, practice ownership, practice size, and provider specialty mix, among others.…”
Section: Datamentioning
confidence: 99%
“…We used data from the 2017 American Board of Family Medicine Family Medicine Certification Examination registration questionnaire. 3 FPs primarily working in EDs and UCCs were identified if they did not provide continuity care and instead indicated ED or UCC as their primary practice setting. FPs covering EDs or UCCs were identified as those who primarily provided continuity care but indicated that they also saw patients in ED or UCC settings.…”
mentioning
confidence: 99%